Pavlov and the Foundation of Behavior Therapy - Plaud, Joseph J. (The Spanish Journal of Psychology, 2003)
The foundation, achievements, and proliferation of behavior therapy have largely been fueled by the movement’s foundation in behavioral principles and theories. Although behavioral accounts of the genesis and treatment of psychopathology differ in the extent to which they emphasize classical or operant conditioning, the mediation of cognitive factors, and the role of biological variables, Pavlov’s discovery of conditioning principles was essential to the founding of behavior therapy in the 1950s, and continues to be central to modern behavior therapy. Pavlov’s reliance on a physiological model of the nervous system, sensible in the context of an early science of neurology, has had an implication for behavior therapists interested in the study of personality types. However, Pavlov’s major legacy to behavior therapy was his discovery of “experimental neuroses,” shown by his students Eroféeva and Shenger-Krestovnikova, to be produced and eliminated through the principles of conditioning and counter-conditioning. This discovery laid the foundation for the first empirically-validated behavior therapy procedure, systematic desensitization, pioneered by Wolpe. The Pavlovian origins of behavior therapy are analyzed in this paper, and the relevance of conditioning principles to modern behavior therapy is demonstrated. It is shown that Pavlovian conditioning represents far more than a systematic basic learning paradigm. It is also an essential theoretical foundation for the theory and practice of behavior therapy.